Embedded wisdom or rooted problems? Aid workers' perspectives on local social and political infrastructure in post‐tsunami Aceh. Issue 2 (28th November 2014) - Daly, Patrick
<x xml:space="preserve">Abstract</x> This paper analyses the role of local social, cultural, and political institutions in post‐disaster reconstruction projects. It contends that such institutions are important considerations within community‐driven reconstruction initiatives, but are often viewed with ambivalence by external aid organisations. This paper draws upon in‐depth qualitative interviews with aid workers involved in the post‐tsunami reconstruction in Aceh, Indonesia, to establish: (i) what roles community institutions were suited to play in the reconstruction; (ii) what were the limitations of community institutions when engaging with external aid agencies; (iii) how did external aid agencies engage with local community institutions; and (iv) how did external aid agencies perceive community institutions.